Estimation and incommutativity in mixed models - Ferreira, Dário (2020)
Submitted by FERREIRA (dario@ubi.pt) on 2020-02-05T17:49:21Z No. of bitstreams: 1 2017 - Estimation and incommutativity in mixed models.pdf: 416003 bytes, checksum: 48413852f90a1b39da78351bac06c8ed (MD5)